أثر ممارسات التسويق الرقمي على تنافسية المؤسسة في ظل أزمة كورونا(منظور إستراتيجي-دراسة ميدانية) دراسة ميدانية لقطاع التجارة في ولاية الأغواط والجزائر العاصمة - بوعزارة إنتصار خولة; ميدون ريان; ريان آمنة (جامعة عمار ثليجي الاغواط, 2022)
This study was aimed at measuring and analysing the impact of digital marketing on the enterprise's competitiveness in view of the Covid-19 crisis in the trade sector in Agouat State and Algiers. The elements of the study were identified by an independent variant of digital marketing with its four tools (social media, video, search engines, email), a modified variant of COVID-19, and another dependent variable of competitive advantage. To achieve these objectives, various relationships between the 36- institution sample variables involving 100 workers in Agouat and Algiers were studied. A questionnaire was designed as a tool to measure the impact of digital marketing on the competitiveness of enterprises in the context of the Covid-19 crisis using the statistical treatment method of the SPSS statistical package.), modelling method of constructive equations and use of the (SMARTPLS3) programme, in order to verify the study's hypotheses. The study found that there is no statistical impact of digital marketing on the competitive advantage and so on the four tools of digital marketing (email - search engines - video marketing - social media marketing) as the latter also had no impact on the competitive advantage.